Management Success Factors in Managing Restaurant Businesses - Suryawan, Ian Nurpatria (Jurnal Ekonomi, 2020)
Restaurant business owners seek to improve their management by analyzing in restaurant business management in Jakarta, Surabaya, Semarang, Bandung, Tangerang and Bekasi. The problem of this research is to find out what factors influence organizational performance. The population of this study were all restaurant business owners (both local and international cuisine) in Jakarta, Surabaya, Semarang, Bandung, Tangerang and Bekasi. The research method used is using non-probability sampling techniques with purposive sampling method. The number of samples was 421 respondents. The results or findings of this study show that there are 4 research hypotheses, namely the positive influence of dynamic capabilities on organization innovation with an alpha of 10%, the positive influence of organization slack on organization performance with an alpha of 5%, the positive influence of organization performance on organizaton performance with an alpha of 5%, Positive influence of dynamic capabilities on organizational performance mediated by organization innovation with alpha 10%. For the other 9 hypothesis testing resulted in unproven conclusions.